2013
DOI: 10.3390/v5030834
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Type I and Type III Interferon Responses in the Central Nervous System

Abstract: The central nervous system (CNS) harbors highly differentiated cells, such as neurons that are essential to coordinate the functions of complex organisms. This organ is partly protected by the blood-brain barrier (BBB) from toxic substances and pathogens carried in the bloodstream. Yet, neurotropic viruses can reach the CNS either by crossing the BBB after viremia, or by exploiting motile infected cells as Trojan horses, or by using axonal transport. Type I and type III interferons (IFNs) are cytokines that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 122 publications
4
45
0
Order By: Relevance
“…A similar study with LACV found nearly no type I IFN-expressing neurons but rather that glia expressed type I IFN (9). In addition, other innate immune pathways, such as the type II and III IFN responses (10,11), and inflammation (12), are activated by viral infection. These observations suggest a great deal of complexity in the brain's response to viral infection and raise several issues in need of clarification.…”
mentioning
confidence: 91%
“…A similar study with LACV found nearly no type I IFN-expressing neurons but rather that glia expressed type I IFN (9). In addition, other innate immune pathways, such as the type II and III IFN responses (10,11), and inflammation (12), are activated by viral infection. These observations suggest a great deal of complexity in the brain's response to viral infection and raise several issues in need of clarification.…”
mentioning
confidence: 91%
“…Thus, brain-resident cells must produce substantial amounts of IFN after virus infection. It appears that all brain cells are capable of producing IFN, although to greatly differing extents (6,7). Most experimental attempts to identify IFN-producing cells in the brain have been in vitro approaches, and only a few of those studies have given insights into the in vivo situation.…”
mentioning
confidence: 99%
“…Typically, neurotropic viruses may reach the central nervous system (CNS) by (i) the olfactory route, (ii) via the blood-brain barrier, (iii) by infecting infiltrating cells, or (iv) by axonal transport (1). Viral clearance in non-neuronal tissues often involves cytolytic elimination of infected cells.…”
mentioning
confidence: 99%